Antidepressant use during pregnancy and serotonin transporter genotype (SLC6A4) Affect newborn serum reelin levels12. Issue 5 (12th June 2012) - Brummelte, S.; Galea, L.A.M.; Devlin, A.M.; Oberlander, T.F.
Abstract This study was undertaken to determine whether altered early serotonin signaling either via gestational serotonin reuptake inhibitor (SRI) exposure or genetic variations in the serotonin transporter promoter region (SLC6A4) alters levels of reelin, an important glycoprotein in neurodevelopment, in mothers and their neonates. Serum reelin protein expression was quantified by immunoblot from maternal and neonatal blood collected at delivery from women taking either an SRI during gestation or controls. SRI‐exposed mothers had higher levels of one reelin fragment, while SRI‐exposed neonates had lower total reelin levels, particularly in females and reelin levels differed with SLC6A4 genotype. Lower neonatal reelin levels predicted less time spent sleeping and more irritability during neonatal behavioral assessment on Day 6 of life. Our results suggest that prenatal SRI exposure and the SLC6A4 genotype influences reelin protein expression in both the mother and newborn and that this may be reflected in neonatal behavior. © 2012 Wiley Periodicals, Inc. Dev Psychobiol 55: 518–529, 2013